The THE ANTICHOLESTEROL ACTIVITY OF BETULINIC ACID AND STIGMASTEROL ISOLATED FROM THE LEAVES OF SUNGKAI (PARONEMA CANESCENS JACK) - MUHARNI, MUHARNI; FERLINAHAYATI, FERLINAHAYATI; YOHANDINI, HENI; RIYANTI, FAHMA; PAKPAHAN, NADYA ANASTASIA PRESCILLA (International Journal of Applied Pharmaceutics, 2021)
Objective: The purpose of this study was to evaluate the anticholesterol activity of Paronema canescens leaves extract. Methods: These compounds were isolated via chromatography using silica gel as the stationary phase. Their structures were revealed using IR and 1D NMR data and by comparing their NMR data with the literature's data. The anticholesterol activity of compounds was tested using photometry via the Liebermann–Burchard reaction. Results: Betulinic acid (1) and stigmasterol (2) were isolated from the leaves extracts of sungkai (P. canescens). The betulinic acid (1) that was isolated showed anticholesterol activity with an IC50 value of 60.53 µg/ml, stigmasterol (2) 222.32 µg/ml, while the standard anticholesterol compound simvastatin had an IC50 of 24.68 µg/ml. Conclusion: The stigmasterol (2) has previously been reported from P. canescens while that of betulinic acid (1) is reported here for the first time and identifies its anticholesterol activity.